Treatment of clinically amyopathic dermatomyositis in adults: a systematic review3. (30th August 2016) - Callander, J.; Robson, Y.; Ingram, J.; Piguet, V.
Summary: Clinically amyopathic dermatomyositis (CADM) affects a subset of 5–20% of patients with dermatomyositis and is defined as the presence of cutaneous features of dermatomyositis without clinical muscle weakness for ≥ 6 months. There is no consensus on first‐line treatment for CADM and whether treatment should differ from treatment of classic dermatomyositis with muscle weakness. We carried out a systematic review of published literature about treatment of adult patients with CADM, via the Embase, Medline, CINAHL and ClinicalTrials.gov databases on 17 February 2015. The aim was to establish which treatments have been used for adult‐onset CADM and what evidence is available regarding the efficacy of these treatments including topical treatments, dapsone, antimalarials, intravenous immunoglobulin (IVIG), nonsteroidal oral immunosuppressants and biological therapies. Eighteen cases series and 42 case reports were found. These provided data on 153 adult patients who met the inclusion criteria. No randomized controlled trials or robust observational studies were found. The majority of patients (60%) had tried more than one treatment due to side‐effects or lack of efficacy. Antimalarial agents were the most commonly used treatment type. In the majority of patients (55%), antimalarial treatments were discontinued due to lack of improvement or inability to wean concomitant steroids. IVIG was the treatment that led to improvement or remission in the greatest proportion of patients. Further robust, high‐quality studies are needed to assess treatment efficacy in CADM without bias. Abstract : What's already known about this topic? Clinically amyopathic dermatomyositis (CADM) is defined as the presence of cutaneous signs of dermatomyositis with no clinical evidence of muscle weakness for ≥ 6 months. CADM affects 5–20% of patients with dermatomyositis and has a significant impact on quality of life. There is no current consensus on the treatment of CADM and no previous systematic reviews have assessed this. What does this study add? This systematic review has established that there are no randomized controlled trials or robust observational studies for treatment of CADM. From the compilation of case series and reports, hydroxychloroquine is the most commonly prescribed treatment for CADM. A proportion of patients have treatment‐resistant disease. In comparison with other treatments, intravenous immunoglobulin led to improvement or remission in the highest proportion of patients included in our review. Linked Editorial: Piguet and Choy. Br J Dermatol 2018;179 :1233–1234 . Plain language summary available online